Men have called her crazy eaudiobook A memoir. - Tendler, Anna Marie (Simon & Schuster Audio, 2024)
* NEW YORK TIMES BESTSELLER* "This book is so many things I didn't know I needed: a testament to the work of healing, a raw howl of anger, and an indictment of misogyny's insipid, predictable, infuriating reign." —Carmen Maria Machado, author of the National Book Award finalist Her Body and Other Parties and the Lambda Literary Award winner In the Dream House A powerful memoir that reckons with mental health as well as the insidious ways men impact the lives of women. In early 2021, popular artist Anna Marie Tendler checked herself into a psychiatric hospital following a year of crippling anxiety, depression, and self-harm. Over two weeks, she underwent myriad psychological tests, participated in numerous therapy sessions, connected with fellow patients and experienced profound breakthroughs, such as when a doctor noted, "There is a you inside that feels invisible to those looking at you from the outside." In Men Have Called Her Crazy , Tendler recounts her hospital experience as well as pivotal moments in her life that preceded and followed. As the title suggests, many of these moments are impacted by men: unrequited love in high school; the twenty-eight-year-old she lost her virginity to when she was sixteen; the frustrations and absurdities of dating in her mid-thirties; and her decision to freeze her eggs as all her friends were starting families. This stunning literary self-portrait examines the unreasonable expectations and pressures women face in the 21st century. Yet overwhelming and despairing as that can feel, Tendler ultimately offers a message of hope. Early in her stay in the hospital, she says, "My wish for myself is that one day I'll reach a place where I can face hardship without trying to destroy myself." By the end of the book, she fulfills that wish.